Real-world outcomes for Chinese breast cancer patients with tumor location of central and nipple portion - Fu, Wei-Da; Wang, Xiao-Hui; Lu, Kang-Kang; Lu, Yi-Qiao; Zhou, Jie-Yu; Huang, Qi-Di; Guo, Gui-Long (Frontiers in Surgery, 2022)
Background: The association between tumor location and breast cancer prognosis has been controversial. We sought to explore the relationship between tumors located in central and nipple portion (TCNP) and Chinese breast cancer. Patients and Methods: A total of 1427 breast cancer patients were recruited. There were 328 cases of TCNP and 1099 cases of tumors in the breast peripheral quadrant (TBPQ). The chi-square test was used to compare different variables between TCNP and TBPQ groups. One-to-one propensity score matching (PSM) was applied to construct a matched sample consisting of pairs of TCNP and TBPQ groups. Kaplan-Meier curves were used for survival analysis of disease-free survival (DFS), breast cancer-specific survival (BCSS) and overall survival (OS). The Cox proportional hazards regression model was applied to identify prognostic risk factors. Results: The median follow-up time was 58 months. Compared to TBPQ, TCNP patients had significantly larger tumor size, more frequent metastasis to lymph nodes (LN) and more proportions of TNM stage II-III. DFS, OS and BCSS rates were markedly lower in the TCNP group as compared to the TBPQ group before and after PSM (all p<0.05). Multivariate Cox analysis showed that TCNP was an independent prognostic factor for breast cancer. Subgroup analysis indicated that for molecular subtypes and TNM stage II-III breast cancer, TCNP were related to worse prognosis. Multivariate logistic regression revealed that TCNP was an independent contributing factor for LN metastasis. Conclusion: In Chinese breast cancer, compared to TBPQ, TCNP is associated with more LN metastasis and poorer prognosis.